2009
DOI: 10.1242/jeb.032854
|View full text |Cite
|
Sign up to set email alerts
|

Bone strength is maintained after 8 months of inactivity in hibernating golden-mantled ground squirrels, Spermophilus lateralis

Abstract: SUMMARYProlonged inactivity leads to disuse atrophy, a loss of muscle and bone mass. Hibernating mammals are inactive for 6-9 months per year but must return to full activity immediately after completing hibernation. This necessity for immediate recovery presents an intriguing conundrum, as many mammals require two to three times the period of inactivity to recover full bone strength. Therefore, if hibernators experience typical levels of bone disuse atrophy during hibernation, there would be inadequate time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 32 publications
7
33
1
Order By: Relevance
“…We saw no evidence of macrostructural cortical bone loss in hibernating ground squirrels, since cortical bone geometrical properties and whole bone mechanical properties were comparable between hibernating and active squirrels (Table1). These results, which are in agreement with a recent finding on the preservation of bone strength in hibernating golden-mantled squirrels (Utz et al, 2009), suggest that 13-lined ground squirrels have adapted to prevent disuse-induced macrostructural cortical bone loss, and that hibernation does not lead to an increased risk of bone fracture upon remobilization. It is, however, unclear whether all hibernating animals experience similar skeletal responses to disuse.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We saw no evidence of macrostructural cortical bone loss in hibernating ground squirrels, since cortical bone geometrical properties and whole bone mechanical properties were comparable between hibernating and active squirrels (Table1). These results, which are in agreement with a recent finding on the preservation of bone strength in hibernating golden-mantled squirrels (Utz et al, 2009), suggest that 13-lined ground squirrels have adapted to prevent disuse-induced macrostructural cortical bone loss, and that hibernation does not lead to an increased risk of bone fracture upon remobilization. It is, however, unclear whether all hibernating animals experience similar skeletal responses to disuse.…”
Section: Discussionsupporting
confidence: 91%
“…Ultimate load, ultimate stress and stiffness of the femurs were not affected by hibernation, suggesting that overall, cortical bone seems to be resistant to disuseinduced bone loss in 13-lined ground squirrels, as was recently demonstrated in golden-mantled ground squirrels (Utz et al, 2009). Therefore, small hibernators, including ground squirrels, may be useful models for investigating biological mechanisms of cortical bone preservation during disuse.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Interestingly, summer (i.e. awake) squirrels that experienced restricted mobility exhibited reduced flexural modulus (stiffness) of the femur when compared with active summer squirrels (Utz et al, 2009). …”
Section: Disuse-induced Osteoporosismentioning
confidence: 99%
“…Early studies suggested that small hibernating mammals such as bats, ground squirrels and hamsters might experience bone loss during hibernation (Kayser and Frank, 1963;Mayer and Bernick, 1959;Whalen et al, 1972). However, more recent data from hibernating S. lateralis squirrels indicate that bone strength and stiffness are unaffected by winter inactivity (Utz et al, 2009). Interestingly, summer (i.e.…”
Section: Disuse-induced Osteoporosismentioning
confidence: 99%